A retrospective observational study analyzing the demographic profile, clinical presentations, and complications of scrub typhus in a tertiary health-care center - Lishal A Misquith; Sowmya Mathew; Anoop Joseph (Asian Journal of Medical Sciences, 2025)
Background: Scrub typhus is an acute febrile illness caused by an obligate intracellular, rickettsial organism, Orientia tsutsugamushi. Around one million cases are reported annually, mostly from the region of the Tsutsugamushi triangle. In India, scrub typhus has been reported from various states. Aims and Objectives: This study was done to analyze the demographic data, clinical presentations, and complications of scrub typhus in our setting. Materials and Methods: A retrospective observational study was done on 65 patients who were admitted to a tertiary health-care center in South India from January 2018 to January 2024 with acute febrile illness and who were diagnosed to have scrub typhus by either scrub typhus immunoglobulin M antibody detection by enzyme-linked immunosorbent assay or Weil Felix OX-K titers >1:160. Demographic data, clinical presentations, treatment details, complications, and outcomes were studied. Results: The most common presenting complaint was fever (96.9%), followed by myalgia (72.3%), headache (55.4%), and vomiting (47.7%). Transaminitis was seen in 55.4% of the patients, thrombocytopenia in 44.61%, and severe thrombocytopenia in 7.6% of the patients. Other complications seen were acute kidney injury (29.2%), pneumonia (29.2%), acute respiratory distress syndrome (ARDS) (10.8%), and meningoencephalitis (7.69%). The majority of our patients (27%) were from the Western Ghat region. Conclusion: Scrub typhus is a serious acute infection that may progress to multiorgan dysfunction and lead to mortality if not treated early. Intensive care requirements and longer hospital stays were higher in patients with central nervous system involvement, ARDS, and those requiring dialysis. A high index of clinical suspicion and prompt treatment are paramount to improve patient outcomes.